2015
DOI: 10.1002/mds.26266
|View full text |Cite
|
Sign up to set email alerts
|

A new F‐box protein 7 gene mutation causing typical Parkinson's disease

Abstract: This is the first time a FBXO7 mutation has been identified that causes a phenotype compatible with typical idiopathic PD and presents with some of its common nonmotor features, such as rapid eye movement sleep behavior disorder, depression, and anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 21 publications
1
54
0
1
Order By: Relevance
“…160 Interestingly, just like the other autosomal recessive forms of PD, it was suggested that FBXO7 is involved in mitophagy. 161 Given its similar phenotype to PARK2-associated PD, the interaction of FBXO7 with PARK2 was examined, and it was shown that reduced expression of FBXO7 leads to reduced translocation of PARK2 to the mitochondria.…”
Section: Fbxo7 and Mitophagymentioning
confidence: 99%
“…160 Interestingly, just like the other autosomal recessive forms of PD, it was suggested that FBXO7 is involved in mitophagy. 161 Given its similar phenotype to PARK2-associated PD, the interaction of FBXO7 with PARK2 was examined, and it was shown that reduced expression of FBXO7 leads to reduced translocation of PARK2 to the mitochondria.…”
Section: Fbxo7 and Mitophagymentioning
confidence: 99%
“…; Lohmann et al . ), These aforementioned side effects occurred in patients with l ‐Dopa‐responsive, idiopathic PD and also in a patient that presented with a pre‐synaptic dopaminergic deficit.…”
Section: Park15 Syndromementioning
confidence: 87%
“…; Lohmann et al . ). But also patients with typical age‐at‐onset and typical clinical symptoms of PD have been identified (Lohmann et al .…”
Section: Park15 Syndromementioning
confidence: 97%
See 2 more Smart Citations